Unraveling The Bottleneck: A Technolegal Approach To Trademark Disputes In The Era Of Technological Disruption - Ricky Thio; Rio Christiawan (LPPM Universitas Trunojoyo Madura, 2023)
Especially in the era of technological disruption where massive changes occur, or refer to considerable changes in how businesses are run caused by technological advances. These changes are accelerating and impacting all aspects of the business, from how products are designed, manufactured, and marketed to how customer service is provided. All businesses have intellectual property, especially new inventors who have emerged in the era of technological disruption. We may not own a patent for our inventions, but we all own a trademark for our business. Trademarks can be images, logos, or terms used to advertise and represent our products. A trademark is a kind of intellectual property right known as a trademark. Therefore legal protection in Indonesia for Mark must be realized. Because globally, the issue of Intellectual Property Rights (IPR) has received serious attention in terms of economic relations or domestic and international trade. Especially countries that have traded products based on Intellectual Property Rights because Intellectual Property Rights are essential because goods and services as trade products are permanently attached to a specific name or entity that differentiates one product from another. There is a